PROBLEMS IN PHARMACOTHERAPY OF RESISTANT ARTERIAL HYPERTENSION - N. V. Teplova; E. O. Taratukhin (Российский кардиологический журнал, 2013)
The paper focuses on the problems in the treatment of patients with resistant arterial hypertension. The relevant recommendations from the European guidelines are presented. Angiotensin receptor antagonists are considered as a group of antihypertensive agents with additional benefits and good tolerability. The evidence on antihypertensive combination therapy is also presented.